Ventisettesimo Rapporto sulle migrazioni 2021 - Fondazione ISMU, [organisation] (FrancoAngeli, 2022)
The ISMU annual Report on migration enters its 27th edition in 2022. Over time, the Report has become a useful reference for people working on migration, both within and outside Italy. This edition analyzes both the impact of the pandemic on migration flows and immigrants and the consequences of the Afghan crisis on migration. As the health emergency subsided in the second half of 2021, public interest on migration resurfaced along with the challenges that migration poses to Italy and the European Union. In addition to the traditional areas of interest (health, work, education, and the legal framework) and to statistical aspects (ISMU estimates that 5,576,000 foreigners live permanently in Italy as of 1st January 2021), the 27th edition of the Report devotes particular attention to the attitudes and orientations of Italian people towards migration, as well as to the experience of migrant women in terms of discrimination and positive valorization. The volume contains in-depth studies on refugees and humanitarian action, on how migration affected local elections, on alternatives to detention, and on foster care for unaccompanied foreign minors. Finally, special attention is devoted to Europe - especially to new directions in EU migration policy after Merkel - and the world - especially bilateral political initiatives involving African countries.